Answer:
54
Step-by-step explanation:
6x + 5x = 99
11x = 99
x=99/11
x=9
6x = 6x9 = 54
5x = 5x9 = 45
<em>ans: </em><u><em>54</em></u>
Answer:
b -3,3 c 6,9 hope this helps
5/8 I believe. You can divide both by 9
Answer:
5.25 miles
Step-by-step explanation:
15 min=1/4 of hour
12/4=3
9/4=2.25
3+2.25=5.25
Answer:
if you meant f(x) = (x - 1) /3 then f (g(x) ) = x
of if you meant f(x) = x - (1/3) then f(g (x)) = 3x + 2/3
Step-by-step explanation:
f(x) = x-1/3 and g(x) = 3x+1 what is (fog)(x)
f ( g(x) ) = (3x + 1) - (1/3) = 3x + 2/3
Or
if you meant f(x) = (x - 1) /3 then f (g(x) ) = x
of if you meant f(x) = x - (1/3) then f(g (x)) = 3x + 2/3